Preserving the tissue profile with immediate implant placement and immediate provisionalization technique - Adityo Widaryono; Sunny Indriani Kurnia; Fatimah Maria Tadjoedin (Wolters Kluwer Medknow Publications, 2022)
Background: Single-tooth replacement in the esthetic zone with a dental implant remains a challenge for clinicians. One challenge is the difficulty of creating a natural tissue profile in the cervical of the implant restoration. In a healed edentulous ridge, multiple surgeries along with hard- and soft-tissue augmentation will be required to gain sufficient tissue volume, thus significantly increasing the patient morbidity. Immediate implant placement, combined with a customized healing abutment, can potentially overcome these difficulties. Case Report: This case report describes the treatment of a patient with a subgingival fracture of the upper central incisor with an implant placement immediately after tooth extraction, xenograft gap filling, and nonfunctional provisional restoration to seal the extraction socket. The incisor had previously undergone root canal treatment and had been restored using a fiber post and ceramic crown. Conclusions: The use of the immediate implant placement with a nonfunctional provisional restoration (immediate implant placement and immediate provisionalization) technique preserves the tissue profile and volume during the implant healing period. This provides the clinician with a natural soft-tissue profile for implant restoration, without the need for an additional surgery.